History of Sheath Rot Disease in Indonesia and Disease Severity in Two Rice Production Centres of West Java - Khoirotul Afifah; Suryo Wiyono; Titiek Siti Yuliani; Baskoro Sugeng Wibowo (Jurnal Perlindungan Tanaman Indonesia, 2020)
The observation conducted from 2000 to 2018 found that rice sheath rot has become an emerging disease in several regions. The disease was able to reduce quality and quantity of rice yield. This research objective was to study the history and status of rice sheath rot caused by Sarocladium oryzae. Data was obtained from literature study, farmer interview, and field survey. Data were used to calculate disease incidence followed by visual observation of the symptoms caused by this disease. Identification of sheath rot pathogen was done using microscopic and molecular techniques using specific primers. Rice sheath rot was first reported in Indonesia as a minor disease in 1987 and has only currently become an important disease. This fungus generally causes rice sheath rot in Karawang and Cianjur Regency. Disease incidence of rice sheath rot was 12.56% without considering the varieties at all generative growth stages. Average disease incidence on all rice varieties observed was 12.64%, except for IR 42 (0%). The level of rice plants damage due to rice sheath rot in Cianjur was higher than Karawang with average disease incidence of 11.58% and 9.27%, respectively. Rice sheath rot symptoms have often been found in the last 10 years with average level of damage of 3%‒18% and yield loss of 10%-15%. This disease has proven to be important and has become a challenge in rice cultivation. The fungus that infect rice plants in Karawang and Cianjur had different morphotypes, namely KP, KP2, KP3, PW3, and PW03. The amplification results showed that all fungal isolates were S. oryzae.